2023
DOI: 10.3390/vaccines11061114
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Disorders following COVID-19 Vaccination

Abstract: Nowadays, people all over the world have been receiving different types of coronavirus disease 2019 (COVID-19) vaccines. While their effectiveness has been well recognized, various post-vaccination disorders are not fully understood. In this review, we discuss neurological disorders related to vascular, immune, infectious, and functional factors following COVID-19 vaccination, and attempt to provide neuroscientists, psychiatrists, and vaccination staff with a reference for the diagnosis and treatment of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 148 publications
(274 reference statements)
0
3
0
Order By: Relevance
“…Another observed cause was immune-mediated damage to the facial nerve. 7 Bell’s palsy is a severe unusual side effect of messenger R.N.A. (mRNA) COVID-19 vaccines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another observed cause was immune-mediated damage to the facial nerve. 7 Bell’s palsy is a severe unusual side effect of messenger R.N.A. (mRNA) COVID-19 vaccines.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Although the precise mechanism of the neurological difficulties induced by COVID-19 vaccines is unknown, numerous theories have been proposed to classify these neurological disorders, including vascular, immunological, infectious, and functional causes. 7 …”
Section: Introductionmentioning
confidence: 99%
“…One group that focused on PASC in the context of the elderly showed that an approximated 30% of patients over the age of 65 developed it ( 190 ), while another study showed that Long COVID symptoms were more severe in elderly patients ( 191 ), supporting data gathered by the US Census Bureau, though it should be noted that the elderly do not have the highest reported incidence rate of post-COVID symptoms following infection ( 192 ). Within the context of vaccination alone, the development of Long COVID has not been extensively addressed, though neuropathic symptoms have been reported, albeit at a lesser occurrence rate than primary infection without vaccination ( 193 195 ). While evidence suggests that those vaccinated before infection have protection against Long COVID ( 196 ), symptom development after vaccination alone is a phenomenon that is not understood and warrants preclinical investigation, particularly in the context of the elderly.…”
Section: Revisiting the Network Hypothesis: Immunoregulatory Effects ...mentioning
confidence: 99%